The Rejection of Interest-Based Loans among Muslim Entrepreneurs and Professionals in Finland - Martikainen, Tuomas (Journal of Muslims in Europe, 2023)
This article discusses religiously motivated financial behaviour among young Muslims in Finland. The aim of the article is to provide empirical knowledge of Islam-based views on rejecting interest-based loans and the implications of this among Finnish Muslims. The research questions are: What are the reasons and motivations for rejecting interest-based bank loans? Are there alternative modes of financing? What are the impacts of rejection on personal investments, including in business and housing? Data were obtained from 18 Finnish Muslim entrepreneurs and professionals who reject interest-based bank loans. The data show that their rejection led to the scope for financial arrangements being more limited, and may also have significant implications for their children, the next generation. To circumvent these consequences, those interviewed used some or all of four alternative models for funding: savings; interest-free loans from family and friends; credit circles; and the time-bound, interest-free repayment period on credit cards.